Characterization of vesicles prepared with various non-ionic surfactants mixed with cholesterol - Manosroi A. (2014)
The vesicles (niosomes) prepared with hydrated mixture of various non-ionic surfactants and cholesterol were studied. The bilayer formation was characterized by X-cross formation under light polarization microscope and the ability of the vesicles to entrap water-soluble substance. Membrane rigidity was measured by means of mobility of fluorescence probe as a function of temperatures. The entrapment efficiencies of the vesicles and microviscosities of the vesicular membrane depended on alkyl chain length of non-ionic surfactants and amount of cholesterol used to prepare vesicles. The stearyl chain (C18) non-ionic surfactant vesicles showed higher entrapment efficiency than the lauryl chain (C12) non-ionic surfactant vesicles. Cholesterol was used to complete the hydrophobic moiety of single alkyl chain non-ionic surfactants for vesicle formation. Niosome prepared with Tween 61 bearing a long alkyl chain and a large hydrophilic moiety in the combination with cholesterol at 1:1 molar ratio was found to have the highest entrapment efficiency of water soluble substances. © 2003 Elsevier Science B.V. All rights reserved.